Caracterización de las algas planctónicas presentes en el humedal la tembladera - Orellana Flores, Kléber Roberto (2013)
The present research focused on determining qualitatively and quantitatively the divisions of algae present in two areas of the lagoon scrapie is located south west of Santa Rosa Canton province of El Oro, and specifically within the jurisdiction of the parish Bellavista by the Railroad Jumón-San Agustin at 17.5 km from Santa Rosa. This investigation lasted three months commencing September 1 of the 2012and ending on November 16of the same year, taking biweekly water samples at the level of the surface area A is located in a water in let from the Arenillas river and in zone B which his located opposite drain. It also took water parameters such as pH, turbidity, dissolved oxygen and temperature, and also performed a chemical analysis to determine ammonium, ammonia, nitrite and nitrate. The collected samples were preserved with 5% formalin and were subsequently taken to the phytoplankton culture laboratory of the Faculty of Agricultural Sciences. Qualitative analysis indicated that the most predominant microscopic algae belonging to the division CLOROPHYTA: Closterium pronum, Ulotrix ehrenbergii and Snedesmus sp. CIANOPHYTA and division: Anabaena constricta and Oscillatoria limosa. The percentages of phytoplankton divisions found in the lagoon are: CLOROPHYTA 52.75%, CIANOPHYTA 36.65%, EUGLENOPHYTA 7.35% and CRYSOPHYTA 3.25%. In the quantitative analysis of phytoplankton is determined that Zone A found 35 750 cel/ml, while in zone B 42 083.3 found cel/ml. Descriptive statistics were used to apply the t test, which indicated no significant difference between the mean sand the null hypothesis is accepted.